1993
DOI: 10.1002/mds.870080311
|View full text |Cite
|
Sign up to set email alerts
|

Axial motor disturbances after hypoxic lesions of the globus pallidus

Abstract: Four subjects aged between 29 and 60 years were examined because of axial motor impairment after hypoxic brain injury. Magnetic resonance imaging revealed circumscribed lesions of the globus pallidus in every case. The association of freezing of the gait, speech disorders, axial bradykinesia, and postural disturbances, with no rigidity or tremor and little or no distal akinesia, suggests a role of the globus pallidus in controlling axial motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…The symptoms of our patient were attributable to the damage of the motor system, including putamen and globus pallidus, as an adverse effect of the hypoxia. However, the sensory system of our patient was intact, which is consistent with previous reports that show that the predominant clinical residues after hypoxic injury of the brain are motor disorders [7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The symptoms of our patient were attributable to the damage of the motor system, including putamen and globus pallidus, as an adverse effect of the hypoxia. However, the sensory system of our patient was intact, which is consistent with previous reports that show that the predominant clinical residues after hypoxic injury of the brain are motor disorders [7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
“…Feve AP and Fenelon G have also suggested that the globus pallidus plays an important role in controlling axial motion. In their study, four patients were examined due to axial motor impairment after hypoxic injury, and MRI scans found lesions of the globus pallidus in all four cases [8]. It is also generally accepted that parkinsonism or axial motor problems are commonly related to the pallidal lesions, and dystonia is related to lesions in the putamen [3].…”
Section: Discussionmentioning
confidence: 99%
“…Feve et al 44 described 4 patients with pure pallidal lesions due to hypoxia who experienced freezing gait, postural impairment, speech disorder, micrographia, and mild appendicular bradykinesia. Similar cases with hypoxia caused by carbon monoxide poisoning have also been reported.…”
Section: Commentmentioning
confidence: 98%
“…Published case reports have included nigropallidal degeneration, 59 pallidonigroluyisian degeneration (PNLD), 60 -62 primary CNS lymphoma, 63 HallervordenSpatz disease 64 and hypoxic ischemic lesions. 65 In addition, PD, diagnosed pathologically, has been shown to have the phenotype of PA with the notable exception of levodopa responsiveness. 66 …”
Section: Pure Akinesiamentioning
confidence: 99%